2019
DOI: 10.1507/endocrj.ej18-0582
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of blood groups in benign thyroid diseases in Turkey

Abstract: İt is known that there is a relationship between some diseases and blood groups. The objective of our study is to investigate how often ABO and Rh blood groups are seen in benign thyroid diseases, especially in autoimmune-mediated thyroid diseases, and hence whether there is an association between blood groups and thyroid diseases. A total of 958 patients who were followed due to any benign thyroid disease were included in the study. The study population comprised 958 patients, 550 with Hashimoto's hypothyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The only local study which estimate the blood group variation and Graves' disease has revealed that significant incidence (43%) of the Graves disorder was seen in patients from blood type O (Aljorany & Abdal 2013). Similarly, in a Turkish study, the blood type O was significantly associated with HT disease (Dağdeviren et al,2019). The high rate of HT in patients with blood type O could be due to the fact that blood type O is the most common blood group in Iraq, hence most of the patients will be of this blood type (Saleh, and Abood, 2016).…”
Section: Resultsmentioning
confidence: 93%
“…The only local study which estimate the blood group variation and Graves' disease has revealed that significant incidence (43%) of the Graves disorder was seen in patients from blood type O (Aljorany & Abdal 2013). Similarly, in a Turkish study, the blood type O was significantly associated with HT disease (Dağdeviren et al,2019). The high rate of HT in patients with blood type O could be due to the fact that blood type O is the most common blood group in Iraq, hence most of the patients will be of this blood type (Saleh, and Abood, 2016).…”
Section: Resultsmentioning
confidence: 93%
“…A study conducted in Ankara in 2019 showed that there may be a relationship between O blood group and Hashimoto's thyroiditis and that the risk of autoimmune thyroid disease may be lower in patients with AB blood group. 18 Some previous studies have shown that the rate of O blood group is higher in some autoimmune diseases such as familial Mediterranean fever, systemic lupus erythematosus, and systemic sclerosis. 7 Since people with O blood group do not have A and B antigens, there are anti-A and anti-B antibodies that develop against them.…”
Section: Discussionmentioning
confidence: 98%
“…In studies, ABO blood group system has been shown to be associated with type 2 diabetes mellitus, chronic renal failure, gestational diabetes mellitus, postpartum depression, coronary artery disease, alopesia areata, gastroduodenal ulcers, Crohn's disease, hepatitis B infection, as well as various cancer types such as stomach, brain, breast, skin cancers and rheumatologic diseases. [5][6][7][8][9][10][11][12][13][14][15][16][17] Although there are recent studies examining the relationship between thyroid diseases and blood group, 18,19 there are no studies examining the relationship between anti TPO positivity and blood groups. The relationship between anti TPO positivity and ABO blood group system is aimed to be investigated by using blood groups which are the product of genetic structure and easy to identify by considering the relationship between anti TPO positivity and blood group.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between ABO blood group and the occurrence and prognosis of chronic inflammatory diseases, such as inflammatory bowel disease and autoimmune diseases have been reported. [60][61][62][63][64][65][66][67][68][69][70][71][72] Chronic inflammation is related to tumor growth, invasion, and migration. [34][35][36] Therefore, we speculate that these inflammatory mediators directly correlate ABO blood groups with tumor development and spread.…”
Section: Dovepressmentioning
confidence: 99%